2021
DOI: 10.1039/d1ra01478a
|View full text |Cite
|
Sign up to set email alerts
|

A novel carbon dot/polyacrylamide composite hydrogel film for reversible detection of the antibacterial drug ornidazole

Abstract: A novel carbon dot/polyacrylamide composite hydrogel film with stable blue fluorescence performance was fabricated by merging a hydrogel film and carbon dots, which was used for highly selective and quantitative detection of ONZ in real samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…1f) could be divided into two peaks at 530.5 and 531.6 eV, which were attributed to CO and C–O. 25–27 These results indicated that the surface of the biomass CDs containing abundant carboxyl and hydroxyl groups had good water solubility, proving that the biomass CDs had been successfully synthesized by microwave.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…1f) could be divided into two peaks at 530.5 and 531.6 eV, which were attributed to CO and C–O. 25–27 These results indicated that the surface of the biomass CDs containing abundant carboxyl and hydroxyl groups had good water solubility, proving that the biomass CDs had been successfully synthesized by microwave.…”
Section: Resultsmentioning
confidence: 83%
“…1c. The peaks at 3431.58 and 2881.15 cm −1 were attributed to the O-H and C-H stretching vibrations, respectively, while the peaks near 1638.54 [25][26][27] These results indicated that the surface of the biomass CDs containing abundant carboxyl and hydroxyl groups had good water solubility, proving that the biomass CDs had been successfully synthesized by microwave.…”
Section: Characterizations Of the Cdsmentioning
confidence: 77%
“…[89] Wu et al prepared carbon dot/polyacrylamide (CDS/PAM) composite hydrogel films with stable fluorescence properties by hydrothermal synthesis using anhydrous citric acid and acrylamide as carbon sources, which can be used for the quantitative detection of the antibacterial drug ornidazole (ONZ). [131] Türk et al prepared pH-sensitive and injectable hydrogels (NCQD/Dox/HA hydrogels) containing nitrogen-doped carbon quantum dots (NCQD), adriamycin (Dox) and hydroxyapatite (HA) by in situ self-crosslinking method through the reaction of nanoquantum dots with Schiff bases, hydrogen bonds and ionic interactions with HA and Dox. [132] Wang et al prepared Cu,N-CQD@GO-CS hydrogels by covalently grafting Cu,N-CQD with GO nanosheets.…”
Section: Biomedical Potential Of Carbon Dot (Cqds) Antibacterial Hydr...mentioning
confidence: 99%